Del Vaingka al Choqueo. Sociabilidad y ritual de los angaité a partir de la colonización del Chaco (1880) - Rodrigo Villagra Carron (Journal de la Société des Américanistes)
From the Vaingka to the Choqueo. Sociability and ritual of the Angaité since the colonization of the Chaco (1880). In this article I explore the relation between social composition and exchange amongst Angaité villages of the Paraguayan Chaco and feasts such as the boy’s initiation ritual called Vaingka and the traditional dance known as Choqueo. I intend to show how the Vaingka has been replaced by the Choqueo since the Paraguayan colonization of the Angaité territory and the Chaco (between 1880 and 1943), and the correlative development of cattle ranches, which constituted the new socio-economic and geographical pattern of reproduction of the indigenous population. In this way, I expect to show how the shifting sequence of these Angaité rituals made possible the interrelation between pre-colonial villages and groups and, later on, following a process of ethnic homogenization of such differences in the ranches, helped to process the alterity of the non indigenous Paraguayan or Chaqueños. In order to do so, I analyze the geographic location and ethnic distinction of the villages of the Western Angaité territory, using the testimonies of aged men and women. In the same vein, I refer to the colonization process and the relocation and integration of such villages into the emerging ranches and Anglican missions. Following this, I describe the Vaingka and explain how this ritual was an occasion of maximum social and productive interaction between the villages and pre-colonial Angaité groups. Finally, I refer to the Choqueo as somehow a substitute of the Vaingka with regards to its social effects, and as a feasible mechanism of dealing with social and ethnic asymmetry in front of the Chaqueños.